Changes in cerebral metabolism in patients with a minimally conscious state responding to zolpidem - Chatelle, Camille; Thibaut, Aurore; Gosseries, Olivia; Bruno, Marie-Aurélie; Demertzi, Athena; Bernard, Claire; Hustinx, Roland; Tshibanda, Luaba; Bahri, Mohamed A.; Laureys, Steven (Frontiers in Human Neuroscience, 2014)
Background: Zolpidem, a short-acting nonbenzodiazepine GABA agonist hypnotic, has been shown to induce paradoxical responses in some patients with disorders of consciousness, leading to recovery of arousal and cognitive abilities. We here assessed zolpidem-induced changes in regional brain metabolism in three patients with known zolpidem response in chronic post-anoxic minimally conscious state. Methods: [18F]-fluorodeoxyglucose positron emission tomography (FDG-PET) and standardized clinical assessments using the Coma Recovery Scale-Revised were performed after administration of 10 mg zolpidem or placebo in a randomized double blind two-day protocol. PET data preprocessing and comparison with a healthy age-matched control group were performed using statistical parametric mapping (SPM8). Results: Behaviorally, all patients recovered functional communication after administration of zolpidem (i.e., emergence from the minimally conscious state). FDG-PET showed increased metabolism in dorsolateral prefrontal and mesiofrontal cortices after zolpidem but not after placebo administration. Conclusion: Our data show a metabolic activation of prefrontal areas, corroborating the proposed mesocircuit hypothesis to explain the paradoxical effect of zolpidem observed in some patients with disorders of consciousness. It also suggests the key role of the prefrontal cortices in the recovery of functional communication and object use in hypoxic patients with chronic minimally conscious state.